Underground coal gasification technology impact on coal reserves in Colombia - Rosso Murillo, John William (Universidad Pedagógica y Tecnológica de Colombia, 2013)
In situ coal gasification technology (Underground Coal Gasification–UCG–) is an alternative to the traditional exploitation, due to it allows to reach the today’s inaccessible coal reserves’ recovery, to conventional mining technologies. In this article I answer the question on how the today’s reserves available volume, can be increased, given the possibility to exploit further and better the same resources. Mining is an important wealth resource in Colombia as a contributor to the national GDP. According with the Energy Ministry (Ministerio de Minas y Energía) [1] mining has been around 5% of total GDP in the last years. This is a significant fact due to the existence of a considerable volume of reserves not accounted for (proved reserves at year 2010 were 6.700 million of tons. Source: INGEOMINAS and UPME), and the coal future role’s prospect, in the world energy production.